Electrochromic Os-based metallo-supramolecular polymers: electronic state tracking by in situ XAFS, IR, and impedance spectroscopies. Issue 41 (29th June 2020) - Yoshida, Takefumi; Bera, Manas Kumar; Narayana, Yemineni S. L. V.; Mondal, Sanjoy; Abe, Hitoshi; Higuchi, Masayoshi
Abstract : In this study, the electronic states of Os-based metallo-supramolecular polymers (poly(OsL) 2+ ) during electrochromism were tracked by in situ X-ray absorption fine structure (XAFS), infrared (IR), and impedance spectroscopies. Abstract : In this study, the electronic states of Os-based metallo-supramolecular polymers (poly(OsL) 2+ ) during electrochromism were tracked by in situ X-ray absorption fine structure (XAFS), infrared (IR), and impedance spectroscopies. The XAFS spectra suggested electronic charge migration in the polymer, and the in situ spectra revealed reversible changes caused by electrochemical redox reactions. The IR spectra of the polymers showed an IVCT band, and we also confirmed the reversible changes by applying a voltage to the redox cell. During the impedance measurements, we found a drastic decrease in the charge transfer resistance ( R CT ) of the polymer films near the electrochemical redox potential.